Independent Language Learning - Bruce Morrison (Hong Kong University Press, 2011)
Independent learning is hardly a new concept. Its twentieth-century roots lie in the work of educators such as Dewey (1916) and Tyler (1949), both of whom emphasised the need for teachers and students to take a greater role in and responsibility for the educational process. Freire (1970) and Illich (1971) contributed liberational concepts of an informal education which lies outside the institutional educational structure, and Knowles (1975, 1980) provided a conceptualisation of andragogy and the self-directed learner which was to underpin the mainstream US post-secondary education system. In the UK tertiary educational context, the work of the Nuffield Group for Research and Innovation in Higher Education (1975), and then the enormous influence of the Council of Europe as reflected in the work of Dickinson (1987), Holec (1980, 1985) and Little (1991), further developed conceptualisations of the autonomous and independent language learner. It is also, however, a field that remains dynamic, with scholars from across the world involved in broadening its scope and deepening our understanding of the various notions it encompasses. Research and areas of expertise embrace many aspects of the field, including the development of learner and teacher autonomy, self-directed and selfaccess learning, technology-mediated pedagogy, assessment in (and of) independent learning and the management of independent learning.